2003
DOI: 10.1046/j.1365-2141.2003.04087.x
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of CD8+ T cells that express low levels of the B cell‐specific molecule CD20 in patients with multiple myeloma

Abstract: Summary. An expanded cytotoxic/memory T‐cell subpopulation expressing low levels of the B‐cell‐specific CD20 molecule was found in peripheral blood and bone marrow of patients with multiple myeloma at the time of diagnosis, but returned to normal levels following treatment. CD3+CD20dim cells were also increased in monoclonal gammopathy of unknown significance albeit at lower levels. Lower CD3+CD20dim cell numbers at baseline may be associated with lack of response to treatment and a poor outcome. Because expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Previous studies also have con rmed that a group of CD3 T cells also express CD20 molecules in the body apart from B cells, which have similar and unique biological characteristics with conventional CD3 T cells [39,40]. Studies have demonstrated that CD3+CD20+ T cells play an important role in multiple diseases [41], such as rheumatoid arthritis [42,43], multiple sclerosis [41], psoriasis [44], lymphoproliferative disorder [45] and cancers [46,47]. In our study, we further indicated that NP or MFS treatment decreased…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies also have con rmed that a group of CD3 T cells also express CD20 molecules in the body apart from B cells, which have similar and unique biological characteristics with conventional CD3 T cells [39,40]. Studies have demonstrated that CD3+CD20+ T cells play an important role in multiple diseases [41], such as rheumatoid arthritis [42,43], multiple sclerosis [41], psoriasis [44], lymphoproliferative disorder [45] and cancers [46,47]. In our study, we further indicated that NP or MFS treatment decreased…”
Section: Discussionsupporting
confidence: 77%
“…Although generally highly regulated and confined to normal and malignant B cells, aberrant CD20 expression is occasionally observed on malignant T cells and has been reported in rare cases of T cell acute lymphoblastic leukemia (T-ALL), non-Hodgkin's lymphoma (T-NHL) and chronic lymphocytic leukemia (T-CLL) as well as on the normal CD8ϩ T cells of multiple myeloma [22][23][24][25][26].…”
Section: Regulation Of Cd20 Expressionmentioning
confidence: 99%